Factors Related To Anxiety Level Of Public Health Employees During COVID-19 - Hubaybah Hubaybah; Sri Astuti Siregar; Fitria Eka Putri; Adelina Fitri; Freety Septika Rahayu (Chakra Brahmanda Lentera Institute, 2022)
Background: Coronavirus is a virus from Wuhan. The impact of the Covid-19 pandemic has caused physical and mental health problems, and this situation is also experienced by all health workers, such as doctors, nurses, midwives, and other health professionals. This study aimed to determine the factors related to the level of anxiety of Puskesmas employees during Covid-19. Methods: The design of this study used a cross-sectional. This research was conducted at the Kemantan Public Health Center, Kerinci Regency. The population of all Kemantan Health Center employees, the number of samples as many as 62 Puskesmas employees. The independent variables of this study were age, gender, education level, economic status, and social support. The dependent variable of this study is the level of anxiety—data analysis using Chi-Square. Results: The results showed that the proportion of the Public Health Center employees who are anxious is higher on inadequate social support (70%) than good social support (34.4%). The bivariate analysis found that poor social support had a risk of 0.634 times for experiencing anxiety, and it was proven that the significant p-value was <0.05 (PR 2.036: 95% CI 1.195-3.470). There is no relationship between age and anxiety levels, and there is no relationship between gender and anxiety levels, there is no relationship between education level and anxiety levels, there is a relationship between economic status and anxiety levels, and there is a relationship between social support and anxiety levels. Conclusion: It was concluded that the variables that had a relationship with the anxiety factors of Public Health Center employees during Covid-19 were economic status and social support. Furthermore, there is no relationship between gender and education level with the anxiety level of the Public Health Center employees at the Kerinci Regency Kerinci Health Center